A preliminary survey of freshwater snails in selected barangays in San Miguel, Leyte - Opleda, November Lily C. (2017)
Gastropods are soft-bodied, single-valve animals of Phylum Mollusca. It is one of the most diverse taxa including over 40,000 species in which 5,000 of these are snails thriving in freshwater habitats. This study aimed to provide a preliminary assessment of the freshwater snails in San Miguel, Leyte. Freshwater snails were collected from three accessible collecting stations within three selected barangays through intensive snail search and random ring sampling on March 2017.